The Business of Jews in the Colony of New York Under English Rule 1664-1774 - Al-Nidawi, Alyaa Zghaier Hussein; Najjar, Kefah Ahmed Mohammed Ahmed (Al-Adab Journal, 2022)
The Jews arrived in the colony of New York after the English took control of it in 1664, to obtain better rights than those obtained under the Dutch rule of the colony and were able to obtain the sympathy of the English leaders in the colony. In 1680, the Jews of the New York colony began trading in the area between New York The builder, however, faced some obstacles in retail trade until 1690, and in a decision of the colony governor of New York Dungan in 1686, the Jew in order to be able to practice a craft and engage in retail trade had to obtain a grant of denial from the governor of the colony and to be naturalized by an act of the Legislative Assembly Then the authority of the city passed the adjective of being free, and by 1688, the situation of the Jews changed and they obtained the rights of free trade in the city, and in 1700 the Jews were able to run their stores and participated in retail trade freely and the merchant Moses Komez became in 1710, the first merchant to export In the year 1730, the number of German-speaking Jewish immigrants to the colony of New York increased, and Jewish shipping merchants developed and became prominent and wealthy merchants after In 1740, after the issuance of the Nationality Law that allowed them to trade throughout the British Empire, and in 1768 the Jew Isaac Moses became one of the founders of the New York Chamber of Commerce, and the work of Jewish merchants was a large and profitable business in the colony, as one of the Jewish merchants, Daniel Combs, participated in trade with the Indies Western, Madeira, Barbados, Curaçao and London, and sent one hundred and thirty-three ships to Curaçao between 1739-1772, and the Jews joined the organization for the work of craftsmen, especially the Seaports Syndicate.